DAMPAK PENGGUNAAN ALAT MESIN PERTANIAN TERHADAP KESEJAHTERAAN PETANI - Dahiri Dahiri (Pusat Kajian Anggaran, 2019)
The large budget of agricultural machine tools is expected to increase rice production so that the welfare level of farmers can also increase. However, this is inversely proportional, because throughout 2011 to 2018 the average level of welfare of farmers reflected in the NTPP is still below 100. Therefore this study purpose to knowing the impact of the use of agricultural machine tools type of two-wheeled tractor, rice trsanplanter, and water pump on welfare of farmers. The data used are secondary data consisting of two-wheeled tractor data, rice transplanters, water pumps, rice production, and NTPP based on provinces in Indonesia from 2011-2017. While the research method used is Structural Equation Modeling (SEM). The results showed that the impact of Alsintan type of two-wheeled tractor and water pump had a positive and significant impact on the production and welfare of farmers. But, the type of rice trsanplanter has a negative and significant impact on the production and welfare of farmers. The recommendations given are firstly the calculation formula for procurement and distribution of agricultural machine tools by calculating the area of land and the level of welfare of farmers. Second, recipients of agricultural machine tools assistance for government agencies in the Province / District or the alsintan brigade are deleted.